STRATEGI PROMOSI PPDB BERDASARKAN ZONASI DI SD NEGERI DAN SWASTA DESA NGADILUWIH KABUPATEN KEDIRI - Azizah, Mamluatul; Sutansi, Sutansi; Untari, Esti (Universitas Negeri Malang, 2021)
Primary school is a level of basic education that opens PPDB activities in May each year. PPDB at all levels is influenced by the zonation policy to equalize and eliminate the predicate of favorite and non-favorite schools. This study aims to find out promotion strategies based on zoning applied in both public and private elementary schools in Ngadiluwih Village and the number of new students based on zoning in elementary schools. Ngadiluwih Village The formulation of the problem in this research is knowing the promotion strategy and the number of students attending public and private elementary schools in Ngadiluwih Village with the zoning policy. This study uses qualitative research with a type of case study research. Data collection uses in-depth interview techniques, questionnaires, and documentation studies. The results showed that the use of the promotion mix in public and private elementary schools in Ngadiluwih village was very diverse. The number of new students in 2019/2020 school year at SDN Ngadiluwih 1 is 55 students, SDN Ngadiluwih 2 is 23 students, SDN Ngadiluvih 3 is 11 students, SD Muhammadiyah 1 Ngadiluwih is at 6, and MI Riyadlotul Uqul is at 29 students, SDN Ngadiluwih 3 at 11 students, SD Muhammadivah 1 Ngadiluwih at 6, and MI Riyadlotul Uqul at 29 students students. So it can be concluded that the promotional mix used is very diverse, and with the zoning policy having an influence on PPDB activities in public elementary schools but not with private primary schools in Ngadiluwih Village.